Testing of the Katrix rotary lobe expander for distributed concentrating solar combined heat and power systems. Issue 2 (11th April 2014) - Norwood, Zack; Kammen, Daniel; Dibble, Robert
Abstract In this article, we present performance results and analysis of a novel rotary lobe expander device. This is part of a larger research effort into the analysis and design of a small‐scale solar system that would compete with available distributed technologies for heat and electricity generation. To choose an appropriate working fluid and components for a distributed concentrating solar combined heat and power (DCS‐CHP) system, we compared many different working fluids, collectors, and expander choices. Of the expanders analyzed, including piston expanders, radial inflow turbines, Tesla turbines, screw expanders, and scroll expanders, the rotary lobe expander shows the greatest promise in small‐scale power applications due to its high efficiency in expanding fluids over large pressure ratios and its low cost to manufacture. This article focuses on testing of a prototype small‐scale expander that was chosen because, to date, no suitable commercial product of less than 10 kW has been found for this application. Initial testing was completed with air to get results that should be indicative of future testing with steam. The test system consists of a compressed air expander (a prototype designed by Katrix, Inc. of Australia) connected to an induction motor driven by a variable frequency drive (VFD) that enables expander testing at varying shaft speeds. Results of the expander testing are reported isentropic efficiencies of 22–25%, thermomechanical efficiencies of 80–95%, and pressure ratios of 6–11 at the tested speeds. Despite mixed results from this particular expander, future refinements could lead to a new class of expanders with low cost and high performance for use in solar combined heat and power and waste‐heat recovery.